2016
DOI: 10.4490/algae.2016.31.6.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of γ-aminobutyric acid-enriched fermented sea tangle (Laminaria japonica) on brain derived neurotrophic factor-related muscle growth and lipolysis in middle aged women

Abstract: This study evaluated the effects of γ-aminobutyric acid (GABA)-enriched fermented sea tangle (GFST), as a functional food, on brain derived neurotrophic factor (BDNF)-related muscle growth and lipolysis, in a sarcopenic obesity highrisk group. Twenty-one middle-aged women (53-63 y) participated in this randomized, double-blind, placebo controlled study. Participants ingested either 1,000 mg of GFST (n = 10) or a sucrose placebo (CON) (n = 11) everyday, for 8 weeks. Subjects were asked to abstain from any regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 54 publications
1
40
0
1
Order By: Relevance
“…These results are supported by a previous study [15] in which FST ingestion for 4 weeks showed no significant effect on GPx activity. However, a longer experimental period may have rendered differing by FST supplementation [20]. Taken together, a longer treatment period, potentially 8 weeks, may be required to demonstrate an enhancement of serum GPx levels in the older women.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are supported by a previous study [15] in which FST ingestion for 4 weeks showed no significant effect on GPx activity. However, a longer experimental period may have rendered differing by FST supplementation [20]. Taken together, a longer treatment period, potentially 8 weeks, may be required to demonstrate an enhancement of serum GPx levels in the older women.…”
Section: Resultsmentioning
confidence: 99%
“…FST was prepared following a recently modified procedure [20]. Sea tangle was added to water at a ratio of 1:15 (w/v) with the addition of yeast extract and glucose, based on the amount of sea tangle added to the mixture.…”
Section: Materials Preparation and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…항산화능이 뛰어난 후코이딘을 함유하고 있으며 [4,5], 콜 레스테롤 배출을 도와 이상지혈증 예방 및 치료에 도움을 주는 [6,7] 난소화성 식이섬유인 알긴산을 함유하고 있다. 다시마를 발효 추출시킬 때 생기는 Gamma aminobutyric acid는 체지방 감소 및 근력 증가에 도움을 주어 남성 갱년기의 주된 증상인 근감소증(sarcopenia)을 완화시키는데 도움을 준다 [8]. 다시마에 는 다양한 기능성물질이 포함되어 있어 다시마에 있는 기능성 물질의 수율을 높이는 연구들도 함께 진행되고 있다 [9].…”
Section: 서 론unclassified
“…Seaweeds are rich in minerals, dietary fibers, proteins, polysaccharides and various marine polyphenols (Choi et al 2016, Fernando et al 2017. Ecklonia cava is a brown seaweed that is abundant in the subtidal regions of Jeju Island in Korea.…”
Section: Introductionmentioning
confidence: 99%